2020
DOI: 10.3390/su12187288
|View full text |Cite
|
Sign up to set email alerts
|

Propelling Children’s Empathy and Friendship

Abstract: Schools play a crucial role in creating supportive and safe environments, and positive feelings are key in fostering such environments. Schools as Learning Communities, based on the dialogic participation of the whole community, are improving social cohesion. However, the underlying processes leading to such transformations remain underexplored. This article suggests that successful educational actions (SEAs) implemented in a school as a learning community, analyzed in this case study, promote positive feeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…An improvement in social relations within the class was also reported as a result of the implementation of online DLGs. This is consistent with other studies that have revealed interactive learning environments to improve both academic improvement (Valero et al, 2018) and friendship relationships among students (León-Jiménez et al, 2020). It is significant in our study that the relationships between students and teachers were not only maintained but also became stronger while doing online DLGs.…”
Section: Discussionsupporting
confidence: 93%
“…An improvement in social relations within the class was also reported as a result of the implementation of online DLGs. This is consistent with other studies that have revealed interactive learning environments to improve both academic improvement (Valero et al, 2018) and friendship relationships among students (León-Jiménez et al, 2020). It is significant in our study that the relationships between students and teachers were not only maintained but also became stronger while doing online DLGs.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous research that evidenced that classical music tends to be linked with certain cognitive and social barriers that prevent some individuals from enjoying it (Sarasúa et al, 2016) However, among transformative elements, according to respondents, participants of these 9 contexts had learnt musical concepts, while important topics related to participants' lives and experience had aroused through the debate about the music. Previous literature has already pointed out the benefits of dialogic learning in both instrumental knowledge (Flecha & Soler, 2013) and values, feelings and relationships (León-Jiménez et al, 2020). Moreover, in the case of the adult school, it must be added that dialogical spaces such as the gatherings promote wellbeing and friendship among older people (León-Jiménez, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Friendship has also proven to be a source of achieving meaning in life among young people (O’Rourke et al, 2019). Relationships based on friendship foster supportive and defending behaviors, as well as preventing others from acting in a violent way (León-Jiménez et al, 2020).…”
Section: State Of the Artmentioning
confidence: 99%